2011
DOI: 10.1194/jlr.p007476
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic variants on lipid parameters and dyslipidemia in a Chinese population

Abstract: This article is available online at http://www.jlr.org on lipid parameters and dyslipidemia in a Chinese population. J. Lipid Res. 2011. 52: 354-360. Supplementary key words genetic polymorphisms • lipid levels • strokeDyslipidemia is a common health problem in developing countries, including China ( 1 ). A vast line of evidence has demonstrated that plasma lipids and lipoprotein concentrations are important risk factors for atherosclerosis and related vascular diseases, which are the leading causes of death i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 31 publications
2
37
1
3
Order By: Relevance
“…(22; 61) A study conducted among a large cohort of Chinese adults (n=4,194) showed that the “T” allele was linked to higher HDL-C level than the “C” allele (p<0.0001). (62) The same pattern was found in a large cohort study of Caucasian adults (n=4,662) with the “C” allele being associated with dyslipidemia-HDL-C (p<0.0001). (63) Our study failed to detect an association between LIPC SNPlcar and various outcomes of interest.…”
Section: Discussionsupporting
confidence: 72%
“…(22; 61) A study conducted among a large cohort of Chinese adults (n=4,194) showed that the “T” allele was linked to higher HDL-C level than the “C” allele (p<0.0001). (62) The same pattern was found in a large cohort study of Caucasian adults (n=4,662) with the “C” allele being associated with dyslipidemia-HDL-C (p<0.0001). (63) Our study failed to detect an association between LIPC SNPlcar and various outcomes of interest.…”
Section: Discussionsupporting
confidence: 72%
“…In a case-control study, which was performed on Han Chinese population analyzing 4192 individuals for type 2 diabetes, the association between elevated triglyceride levels and genotypes for MLXIPL rs17145738 variant and for GCKR rs780094 was confirmed, but not for GALNT2 rs4846914 polymorphism [46].…”
Section: Discussionmentioning
confidence: 90%
“…These associations were primarily found in European ancestry. Following studies successfully replicated most of these loci in East Asian population [12], [13], [14], [15], [16], [17]. However, some of the loci showed no significant association with lipid and lipoprotein levels in Asian population, including the MAFB , NCAN/CLIP2/PBX4 and MVK/MMAB loci [12], [14], [17].…”
Section: Introductionmentioning
confidence: 93%